Local BMP2 hydrogel therapy for robust bone regeneration in a porcine model of Legg-Calvé-Perthes disease - Chi Ma; Min Sung Park; Felipe Alves do Monte; Vishal Gokani; Olumide O. Aruwajoye; Yinshi Ren; Xiaohua Liu; Harry K. W. Kim (npj Regenerative Medicine, 2023)
Abstract Legg-Calvé-Perthes disease is juvenile idiopathic osteonecrosis of the femoral head (ONFH) that has no effective clinical treatment. Previously, local injection of bone morphogenetic protein-2 (BMP2) for ONFH treatment showed a heterogeneous bone repair and a high incidence of heterotopic ossification (HO) due to the BMP2 leakage. Here, we developed a BMP2-hydrogel treatment via a transphyseal bone wash and subsequential injection of BMP2-loaded hydrogel. In vitro studies showed that a hydrogel of gelatin-heparin-tyramine retained the BMP2 for four weeks. The injection of the hydrogel can efficiently prevent leakage. With the bone wash, the injected hydrogel had a broad distribution in the head. In vivo studies on pigs revealed that the BMP2-hydrogel treatment produced a homogeneous bone regeneration without HO. It preserved the subchondral contour and restored the subchondral endochondral ossification, although it increased growth plate fusions. In summary, the study demonstrated a promising BMP2-hydrogel treatment for ONFH treatment, especially for teenagers.